Multiple Venous Malformations as a Cause of Pulsatile Tinnitus - Al Afif, Ayham; Alamoudi, Uthman; Al-Sayed, Ahmed A.; Bance, Manohar (Case Reports in Otolaryngology, 2020)
Introduction. Pulsatile tinnitus is a relatively common presentation in otolaryngology clinics, most cases of which have a treatable cause. This presentation warrants a thorough workup to identify treatable, and rule out life-threatening, etiologies. We present a case of a patient with pulsatile tinnitus arising from multiple dilated venous channels in the head and neck. Case Presentation. We present the case of a 65-year-old Caucasian female with a two-year history of progressive, bilateral pulsatile tinnitus, which had become debilitating. Computed-tomographic angiography (CTA) studies ruled out an intracranial vascular cause for her symptoms. However, computed tomography (CT) scanning and magnetic resonance imaging (MRI) revealed multiple dilated bilateral, low-flow, venous channels throughout the head and neck. The proximity of such dilated venous channels to the temporal bone provides a route for sound to be transmitted to the inner ear. Conclusion. Arterial, venous, and systemic etiologies can cause pulsatile tinnitus. Arteriovenous malformations (AVMs) of the head and neck represent less than 1% of cases. In our patient, dilated low-flow venous malformations are the likely source of her symptoms, which is the first reported case in the literature.